Preparation method of high-performance compact microporous sintered corundum material

By combining sintered corundum fine powder and additives such as silicon carbide fiber, dense microporous sintered corundum material is prepared, which solves the creep and brittleness of the guide blades in extreme high temperature environments, and achieves the high mechanical and thermodynamic properties of the material.

CN119683972AActive Publication Date: 2025-03-25JIANGSU JINGXIN NEW MATERIAL
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411909001.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-25
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

Existing materials have problems of creep, brittleness and processing difficulty in extremely high temperature environments of guide blades of aerospace engines, and it is difficult to meet the mechanical properties, thermodynamic properties and chemical stability requirements of guide blades.

Method used

Sintered corundum fine powder is used as the main raw material, and by adding silicon carbide fibers and sintering aids, mixing them evenly with polyvinyl alcohol solution, isostatically molded, and sintering is carried out at high temperature under a protective atmosphere to prepare dense microporous sintered corundum material.

Benefits of technology

The material performs excellently in extreme high temperature environments, has excellent oxidation resistance, thermal corrosion resistance and mechanical properties, and can effectively resist particle erosion and wear in the gas stream, and maintain its shape under high temperature and stress.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683972A_ABST
    Figure CN119683972A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new material preparation, and discloses a preparation method of a high-performance compact microporous sintered corundum material. The sintered corundum fine powder is firstly prepared, the fine powder has the characteristics of large crystal grains, multiple pores, fine pores, low heat conductivity coefficient and the like, and the high-performance compact microporous sintered corundum material prepared by taking the fine powder as a main raw material has the properties of high temperature resistance, oxidation resistance, corrosion resistance and the like, also has excellent thermal shock resistance, can be used in a severe working environment, and is suitable for industrial production. Such as airspace engine guide vanes. In addition, the corundum material obtained by the preparation method disclosed by the invention can also be applied to other fields requiring high temperature resistance, high mechanical strength and good thermal stability, such as industrial furnace linings, high-temperature sensor protection covers and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of new material preparation, and specifically relates to a method for preparing a high-performance dense microporous sintered corundum material. Background Art

[0002] In aerospace engines, guide vanes are key components located after the combustion chamber and before the turbine. Their main function is to guide the high-temperature and high-pressure gas flow to impact the turbine blades at the optimal angle, thereby maximizing the efficiency of the turbine. In the combustion chamber of an aircraft engine, after the fuel is mixed with the oxidizer and ignited, the temperature of the generated gas can reach over 2000°C. The guide vanes are directly exposed to this extreme high temperature environment and need to be able to withstand this high temperature for a long time without melting or significant deformation. In addition to continuous high temperatures, the engine also undergoes frequent thermal cycles during startup, acceleration, deceleration and shutdown. These thermal cycles can cause thermal stresses inside the material, which may cause cracks to form and propagate, thus affecting the service life of the blades.

[0003] Since the working environment of the guide vanes is extremely harsh, including extremely high temperature, pressure and particle erosion in high-speed airflow, very high requirements are placed on the selection of guide vane materials.

[0004] In terms of mechanical properties: Tensile strength: The guide vanes need to have sufficient tensile strength to resist the impact and centrifugal force of the gas flow. Wear resistance: The high-speed gas flow contains fine solid particles, which will cause wear on the blade surface. Therefore, the guide vane material needs to have good wear resistance. Creep resistance: Under high temperature and stress, the material may creep, that is, slow plastic deformation. This will affect the shape accuracy and structural integrity of the blade.

[0005] In terms of thermodynamic properties: Low thermal conductivity: In order to reduce the transfer of heat to other parts of the engine, the guide vane material should have a low thermal conductivity to maintain good thermal insulation. Thermal expansion coefficient: The thermal expansion coefficient of the material should be as low as possible to reduce internal stress caused by temperature changes.

[0006] The materials used in the prior art all have their limitations, such as nickel-based superalloys: the nickel-based superalloys widely used at present have good comprehensive properties, but they still have certain limitations under extreme high temperature conditions, such as creep problems after long-term use. For example, ceramic materials: traditional ceramic materials such as zirconium dioxide have good high temperature resistance, but their brittleness and processing difficulty limit their application in complex shape parts.

[0007] Existing materials and technologies are still insufficient in meeting the demanding requirements of aerospace engine guide vanes. Therefore, the development of a new type of high heat-resistant material, especially one with excellent mechanical properties, thermodynamic properties and chemical stability, is crucial to improving the overall performance and reliability of the engine. Summary of the invention

[0008] Purpose of the invention: In view of the shortcomings in the prior art, the present application provides a method for preparing a high-performance dense microporous sintered corundum material. The sintered corundum material prepared by the method of the present invention has excellent mechanical properties, thermodynamic properties and chemical stability, and can be used in harsh working environments.

[0009] Technical solution: The preparation method of the high-performance dense microporous sintered corundum material provided by the present invention uses sintered corundum fine powder as the main raw material, and the sintered corundum fine powder has a volume density of 3.65-3.69g / cm 3 , the grain size is 100-300 μm, and the thermal conductivity is less than 1.8 W / (m·K); silicon carbide fiber and sintering aid are added, and then mixed evenly with polyvinyl alcohol solution, and isostatically pressed into a preform; the preform is placed in a furnace, heated to 850-900° C. under a protective atmosphere, kept warm for 2-2.5 hours, and then continued to heat to 1700-1800° C., kept warm for 4-5 hours, and naturally cooled to room temperature after sintering to obtain the dense microporous sintered corundum material.

[0010] Specifically, the sintered corundum fine powder is obtained by the following method: 94-96 parts of α-Al2O3 powder, 1-3 parts of aluminum hydroxide powder, 0.5-2 parts of metal aluminum powder and 0.2-0.8 parts of additives are mixed, and the mixture is evenly ground; the ground powder is balled to form a ball blank with a diameter of 30±2mm, the water content of the ball blank is about 20%, and the ball blank is dried to a water content of less than 1%, calcined, cooled after calcination, crushed and ball-milled to obtain the sintered corundum fine powder.

[0011] The raw materials for preparing sintered corundum fine powder contain a small amount of aluminum hydroxide, which will decompose into aluminum oxide and water vapor at high temperature. This process will occur before or during sintering. Aluminum hydroxide will produce certain gases (water vapor) during the decomposition process. These gases will form a small pressure between the powder particles, which will help the rearrangement of the material, thereby promoting densification during the sintering process. Due to the thermal decomposition characteristics of aluminum hydroxide, it can change the microstructure of the final product during the heating process, such as affecting the grain size, shape and distribution, and then affecting the mechanical properties and other physical and chemical properties of the material. However, the addition amount of aluminum hydroxide must be strictly controlled, because excessive addition may lead to adverse consequences, such as the generation of too many pores or undesirable phase changes. Therefore, for the present invention, the addition amount of aluminum hydroxide is preferably 1.5 to 2 parts.

[0012] At high temperatures, when trace amounts of metallic aluminum powder in the raw materials come into contact with water vapor, in addition to forming aluminum oxide, hydrogen (H2) is also produced, which expands inside the material to form pores. By adjusting the particle size, addition amount, sintering temperature and time of the aluminum powder, the size, shape and distribution of the pores produced can be effectively controlled to obtain the desired microstructure. The amount of aluminum powder needs to be precisely controlled. Excessive amounts may lead to excessive pores, affecting the mechanical properties of the product; insufficient amounts will not achieve the expected pore-forming effect. Fine particles are more easily dispersed evenly in the alumina powder, which helps to form a uniformly distributed pore structure. If the particles are too large, it may be difficult to disperse evenly, resulting in excessively violent local reactions and uneven pores. At the same time, finer aluminum powder has a larger specific surface area, which increases its chances of contact with water vapor or oxygen, thereby increasing the reaction rate. However, overly fine aluminum powder may cause handling difficulties and increase safety risks (such as spontaneous combustion or explosion). Therefore, it is necessary to balance the reaction activity and operational safety. For the present invention, the metal aluminum powder preferably has a particle size between 10 and 50 microns, and the addition amount is preferably 0.8-1 part.

[0013] Specifically, the additives are: magnesium oxide and silicon dioxide. A trace amount of magnesium oxide is used to promote sintering densification, and a trace amount of SiO2 is used to improve the dispersibility of the micropowder. The addition amount is 0.2-0.5 parts of magnesium oxide and 0.1-0.3 parts of silicon dioxide, preferably 0.2 parts of magnesium oxide and 0.1 parts of silicon dioxide.

[0014] Specifically, the grinding is to grind the mixture in a continuous ball mill to a D50 of 5±0.1 μm.

[0015] Specifically, the calcination process is as follows: the temperature is raised from room temperature to 250°C and kept warm. The decomposition temperature of aluminum hydroxide is usually between about 200°C and 450°C. Then the temperature is quickly raised to 800°C and kept warm for hours. The effective temperature range for the reaction of aluminum powder and water vapor is roughly 700°C to 1000°C. This stage is crucial for metallic aluminum powder because it can react with the remaining water vapor to generate Al2O3 within this temperature range. Therefore, the specific heating process is as follows: the temperature is raised from room temperature to 250°C, kept warm for 1 to 3 hours, and then quickly raised to 800°C and kept warm for 1 to 3 hours. More specifically, the heating process is as follows: the temperature is raised from room temperature to 250°C within 1 hour, kept warm at 250°C for 2 hours, quickly raised to 800°C within 30 minutes, kept warm for 2 hours, and raised to 1920°C within 6 hours.

[0016] Specifically, the cooling is performed along with the cooling of the kiln to below 80°C.

[0017] Specifically, the usage ratio of the sintered corundum fine powder, silicon carbide fiber, sintering aid, and polyvinyl alcohol solution is: 100 parts of sintered corundum fine powder, 5-10 parts of silicon carbide fiber, 1-3 parts of sintering aid, and 4-6 parts of polyvinyl alcohol solution. Preferably, 100 parts of sintered corundum fine powder, 8 parts of silicon carbide fiber, 2 parts of sintering aid, and 5 parts of polyvinyl alcohol solution are used.

[0018] Specifically, the sintering aid is titanium dioxide. The addition of titanium dioxide can promote particle bonding, improve the strength and wear resistance of the sintered product, and at the same time, inhibit grain growth and improve the fineness and uniformity of the sintered product. In addition, titanium dioxide can form a solid solution with the sintered material, reduce the sintering temperature, and accelerate diffusion and sintering speed.

[0019] Beneficial effects: The sintered corundum material prepared by the method of the present invention performs well in extremely high temperature environments, can withstand temperatures exceeding 2000°C in the combustion chamber, and has excellent oxidation resistance and thermal corrosion resistance. It is not easy to react with oxygen to form oxides, and has high resistance to most acid and alkali solutions and gases. In addition, the material has enhanced mechanical properties, extremely high hardness and strength, and can effectively resist particle erosion and wear in the gas flow; by introducing reinforcing phases such as silicon carbide fibers, the toughness of the material is significantly improved, and it can better absorb the energy generated by thermal shock and avoid rapid crack expansion. In addition, the larger grain size helps to improve the creep resistance of the material, and it can still maintain its shape under continuous high temperature and stress.

[0020] The sintered corundum prepared by the method of the present invention also has excellent thermodynamic properties, including lower thermal conductivity and thermal expansion coefficient, which can effectively isolate heat, reduce the heat transferred from the combustion chamber to other parts of the engine, protect the external structure from overheating damage, and reduce the internal stress caused by temperature changes to prevent material cracking. At the same time, it has good processing performance and can be made into complex geometric shapes through advanced molding technology to meet the design requirements of the guide vanes, and ensure reliable connection with other engine components through appropriate joining technology. Although high-quality sintered corundum and its processing costs are relatively high, optimizing the production process and economies of scale can help to gradually reduce the unit cost, and the long life and high reliability of the material reduce the cost of maintenance and replacement, making it economical. In addition, sintered corundum is a non-toxic, harmless, recyclable and reusable material that meets the requirements of sustainable development.

[0021] In addition to aerospace engine guide blades, this high-performance sintered corundum material can also be used in other fields that require high temperature resistance, high mechanical strength and good thermal stability, such as industrial furnace linings, high-temperature sensor protection covers, etc. In summary, the sintered corundum material and preparation method provided by the present invention not only overcome the limitations of existing materials in high temperature environments, but also greatly improve the comprehensive performance of the material through fiber reinforcement technology, providing strong technical support for the development of the aviation industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the SEM electron microscope image of the material obtained in Example 1 (100 μm)

[0023] Figure 2 This is the SEM electron microscope image (50 μm) of the material obtained in Example 1

[0024] Figure 3 This is the SEM electron microscope image of the material obtained in Example 1 (10 μm)

[0025] Figure 4 SEM electron microscope image of sintered corundum of comparative example 1 (20 μm)

[0026] Figure 5 SEM electron microscope image of sintered corundum of comparative example 1 (10 μm)

[0027] Figure 6 This is the SEM electron microscope image of the sintered corundum in comparative example 2. DETAILED DESCRIPTION

[0028] The technical solution of the present application is described in detail below through examples, but the protection scope of the present application is not limited to the examples. The parts described in the present invention are all calculated by mass.

[0029] Example 1

[0030] Weigh 95 parts of high-purity (99.5% or more) α-Al2O3 powder, 1.8 parts of aluminum hydroxide powder, 0.9 parts of metallic aluminum powder, 0.2 parts of magnesium oxide, and 0.1 parts of silicon dioxide, mix the above raw materials, grind them after mixing evenly, and grind the mixture in a continuous ball mill to a D50 of about 5 microns; then make a ball blank with a diameter of about 30 mm in a ball forming machine; dry it at 90°C to control its water content below 1%; calcine it in an ultra-high temperature vertical kiln, and the heating process is: rise from room temperature to 250°C within 1 hour, keep it at 250°C for 2 hours, quickly heat it to 800°C within 30 minutes, keep it for 2 hours, heat it to 1920°C within 6 hours, and finally calcining temperature is about 1920°C, keep it for 4 hours, and then cool it with the kiln to below 80°C; the sintered block is preliminarily crushed by a Barmac crusher, and then ball milled by a ball mill to obtain the sintered corundum fine powder. Its SEM electron microscope image is as follows Figure 1 , Figure 2 , Figure 3 shown.

[0031] Comparative Example 1

[0032] The SEM electron microscope image of the currently available sintered corundum is as follows: Figure 4 , Figure 5 shown.

[0033] Comparative Example 2

[0034] The SEM electron microscope image of the currently available sintered corundum is as follows: Figure 6 shown.

[0035] By comparing the electron microscope images of the embodiment and the comparative example, it can be seen that the grain size of the existing commercially available sintered corundum is basically around 20-40μm, and some grains are around 50μm; while the grain size of the product obtained in this embodiment is larger and the crystallization is more complete. It can also be seen that the existing sintered corundum has fewer pores, and the pores are uneven in size. Due to the looseness between the grain boundaries, there are also many pores at the grain boundaries (such as Figure 5 ), and even some grains have basically no pore distribution, thus losing the excellent thermal shock resistance of sintered corundum (such as Figure 6 ). The product obtained in this embodiment has a large number of pores, which are fine and distributed in the crystal. The crystal structure and pore distribution are as follows: Figure 2 , Figure 3 As shown in FIG. 1 , due to having more fine pores, the thermal conductivity of the sintered corundum is reduced by more than 30% compared with the thermal conductivity of the existing commercially available sintered corundum.

[0036] Example 2

[0037] Weigh 95 parts of high-purity (99.5% or more) α-Al2O3 powder, 1.8 parts of aluminum hydroxide powder, 0.9 parts of metal aluminum powder, 0.2 parts of magnesium oxide, and 0.1 parts of silicon dioxide, mix the above raw materials, grind them after mixing evenly, and grind the mixture in a continuous ball mill to a D50 of about 5 microns; then make a ball blank with a diameter of about 30 mm in a ball forming machine; dry it at 90°C to control its water content below 1%; calcine it in an ultra-high temperature vertical kiln, and the heating process is: rise from room temperature to 250°C within 1 hour, keep it at 250°C for 2 hours, rise to 800°C within 2 hours, keep it at 2 hours, and rise to 1920°C within 6 hours. The final calcination temperature is about 1920°C, keep it at 4 hours, and then cool it with the kiln to below 80°C; the sintered block is preliminarily crushed by a Barmac crusher, and then ball-milled by a ball mill to obtain the sintered corundum fine powder.

[0038] Example 3

[0039] Weigh 95 parts of high-purity (99.5% or more) α-Al2O3 powder, 1.8 parts of aluminum hydroxide powder, 0.9 parts of metallic aluminum powder, 0.2 parts of magnesium oxide, and 0.1 parts of silicon dioxide, mix the above raw materials, grind them after mixing evenly, and grind the mixture in a continuous ball mill to a D50 of about 5 microns; then make a ball blank with a diameter of about 30 mm in a ball forming machine; dry it at 90°C to control its water content below 1%; calcine it in an ultra-high temperature vertical kiln, and the heating process is: rise from room temperature to 250°C within 1 hour, then rise to 800°C within 2 hours, keep it warm for 2 hours, rise to 1920°C within 6 hours, and finally calcinate it at a temperature of about 1920°C, keep it warm for 4 hours, and then cool it to below 80°C with the kiln; the sintered block is preliminarily crushed by a Barmac crusher, and then ball-milled by a ball mill to obtain the sintered corundum fine powder.

[0040] The relevant test data of Examples 1 to 3 and Comparative Example 1 are shown in the following table:

[0041]

[0042]

[0043] It can be seen from the data in the table that, compared with the existing sintered corundum, the embodiment of the present invention has a larger bulk density, a larger grain size, and a lower thermal conductivity.

[0044] In addition, it can be seen that the heating method affects the thermal conductivity of the product. The reason is that the heating method affects the formation of pores. Example 1 can better form more fine pores, so its thermal conductivity is the lowest.

[0045] Example 4

[0046] The sintered corundum fine powder obtained in Example 1 is used as the main raw material, and is mixed according to the following ratio: 100 parts of sintered corundum fine powder, 8 parts of silicon carbide fiber, 2 parts of titanium dioxide, and 5 parts of polyvinyl alcohol solution. The mixture is evenly mixed, and a long strip guide blade preform is pressed by a cold isostatic press at a pressure of 200 MPa; the preform is placed in a furnace, heated to 850°C under a nitrogen protective atmosphere, kept warm for 2 hours, and then continued to heat to 1750°C, kept warm for 4 hours, and naturally cooled to room temperature after sintering to obtain the dense microporous sintered corundum material.

[0047] Example 5

[0048] The sintered corundum of Example 2 is used as the main raw material and mixed according to the following ratio: 100 parts of sintered corundum, 8 parts of silicon carbide fiber, 2 parts of titanium dioxide, and 5 parts of polyvinyl alcohol solution. The mixture is evenly mixed and pressed into a long strip guide blade preform under a pressure of 200 MPa by a cold isostatic press; the preform is placed in a furnace, heated to 850°C under a nitrogen protective atmosphere, kept warm for 2 hours, and then continued to heat to 1750°C, kept warm for 4 hours, and naturally cooled to room temperature after sintering to obtain the dense microporous sintered corundum material.

[0049] Example 6

[0050] The sintered corundum fine powder obtained in Example 3 is used as the main raw material, and is mixed according to the following ratio: 100 parts of sintered corundum fine powder, 8 parts of silicon carbide fiber, 2 parts of titanium dioxide, and 5 parts of polyvinyl alcohol solution. The mixture is evenly mixed, and a long strip guide blade preform is pressed by a cold isostatic press at a pressure of 200 MPa; the preform is placed in a furnace, heated to 850°C under a nitrogen protective atmosphere, kept warm for 2 hours, and then continued to heat to 1750°C, kept warm for 4 hours, and naturally cooled to room temperature after sintering to obtain the dense microporous sintered corundum material.

[0051] Example 7

[0052] The sintered corundum of comparative example 1 is used as the main raw material, and is mixed according to the following ratio: 100 parts of sintered corundum fine powder, 8 parts of silicon carbide fiber, 2 parts of titanium dioxide, and 5 parts of polyvinyl alcohol solution. The mixture is evenly mixed, and a long strip guide blade preform is pressed by a cold isostatic press at a pressure of 200 MPa; the preform is placed in a furnace, heated to 850°C under a nitrogen protective atmosphere, kept warm for 2 hours, and then continued to heat to 1750°C, kept warm for 4 hours, and naturally cooled to room temperature after sintering to obtain the dense microporous sintered corundum material.

[0053] The samples obtained in Examples 4 to 7 were tested by using 448 kPa compressed air to spray 1000 g ± 5 g of standard silicon carbide sand (36#) on the samples within 450 s ± 15 s, and the weight loss rate was calculated. After soaking in a 10% mass fraction NaOH solution at room temperature for 15 days, the weight loss rate was calculated. After keeping warm in an oxygen atmosphere at 800°C for 5 days, the weight gain rate was calculated. The specific results are shown in the following table:

[0054]

[0055] Example 4 and Example 5 were tested. The samples were placed in an electric furnace (1000°C, 1500°C, 2000°C) for 15 minutes, taken out and air-cooled. After 30 minutes, the samples were placed in the electric furnace for heating, insulation and cooling. The process was repeated many times until cracks or fractures appeared on the samples. The number of thermal shocks before the samples were destroyed was recorded.

[0056]

[0057] It can be seen that the material of the present invention has excellent wear resistance, corrosion resistance, high temperature resistance and thermal shock resistance. Further, by comparing Examples 4 to 7, it can be found that the materials obtained in Examples 4 to 6 are significantly better than Example 7 in terms of high temperature resistance and thermal shock resistance.

[0058] The present invention forms a large number of uniformly distributed and size-controllable tiny pores inside the corundum material through an optimized preparation process. The difference in thermal expansion coefficients between the air in the pores and the alumina matrix is ​​small, so that the two can better cooperate to expand or contract when the temperature changes, reducing the internal stress caused by thermal expansion mismatch. When external thermal shock causes cracks to expand in the ceramic matrix, the cracks are prone to deflect, bifurcate or be pinned after encountering pores. This phenomenon shortens the crack length, increases the number, and forms a complex network structure. This not only increases the energy required for the material to break, but also effectively inhibits the further expansion of the cracks. The uniformly distributed tiny pores can act as a "buffer" during the rapid cooling and heating process, effectively absorbing and dispersing the thermal stress caused by the rapid temperature change, thereby reducing the impact on the matrix structure and further enhancing the material's resistance to thermal shock.

[0059] The above description is only a preferred embodiment of the present application and is not intended to limit the present application.

Claims

1. A method for preparing a dense microporous sintered corundum material, characterized in that: The main raw material is sintered corundum fine powder, the bulk density of which is 3.65-3.69 g / cm 3 , the grain size is 100-300 μm, and the thermal conductivity is less than 1.8 W / (m·K); silicon carbide fiber and sintering aid are added, and then mixed evenly with polyvinyl alcohol solution, and isostatically pressed into a preform; the preform is placed in a furnace, heated to 850-900° C. under a protective atmosphere, kept warm for 2-2.5 hours, and then continued to heat to 1700-1800° C., kept warm for 4-5 hours, and naturally cooled to room temperature after sintering to obtain the dense microporous sintered corundum material.

2. The method for preparing dense microporous sintered corundum material according to claim 1, characterized in that: The sintered corundum fine powder is obtained by the following method: 94-96 parts of α-Al2O3 powder, 1-3 parts of aluminum hydroxide powder, 0.5-2 parts of metal aluminum powder and 0.3-0.8 parts of additives are mixed, and the mixture is evenly ground; the ground powder is balled to form a ball blank with a diameter of 30±2mm, which is dried to a water content of less than 1%, calcined, cooled after calcination, crushed and ball-milled to obtain the sintered corundum fine powder.

3. The method for preparing the dense microporous sintered corundum material according to claim 2, characterized in that: The particle size of the metal aluminum powder is between 10 and 50 μm, and the added amount is 0.8-1 part.

4. The method for preparing dense microporous sintered corundum material according to claim 2, characterized in that: The additives are: 0.2-0.5 parts of magnesium oxide and 0.1-0.3 parts of silicon dioxide.

5. The method for preparing dense microporous sintered corundum material according to claim 2, characterized in that: The grinding is to grind the mixed material in a continuous ball mill to a D50 of 5.0±0.1 μm.

6. The method for preparing dense microporous sintered corundum material according to claim 2, characterized in that: The calcination process is as follows: the temperature is raised from room temperature to 250°C, kept at this temperature for 1 to 3 hours, then quickly raised to 800°C, kept at this temperature for 1 to 3 hours, and then raised to 1920°C.

7. The method for preparing dense microporous sintered corundum material according to claim 6, characterized in that: The heating process is as follows: from room temperature to 250°C within 1 hour, kept at 250°C for 2 hours, quickly heated to 800°C within 30 minutes, kept for 2 hours, and heated to 1920°C within 6 hours.

8. The method for preparing dense microporous sintered corundum material according to claim 2, characterized in that: The cooling is performed along with the cooling of the kiln to below 80°C.

9. The method for preparing dense microporous sintered corundum material according to claim 1, characterized in that: The usage ratio of the sintered corundum fine powder, silicon carbide fiber, sintering aid and polyvinyl alcohol solution is: 100 parts of sintered corundum fine powder, 5-10 parts of silicon carbide fiber, 1-3 parts of sintering aid and 4-6 parts of polyvinyl alcohol solution.

10. The method for preparing dense microporous sintered corundum material according to claim 9, characterized in that: The sintering aid is titanium dioxide.

Citation Information

Patent Citations

  • Preparation method of alumina with intensive mesopore diameter distribution

    CN102120599A

  • Micro-porous high-strength anti-corrosion corundum refractory aggregate and preparation method thereof

    CN102659426A

  • Aluminum-magnesium lightweight refractory material and preparation method thereof

    CN103044048A

  • Preparation method for microporous light-weight corundum fireproof aggregate

    CN103145428A

  • Corundum aggregate with micro-nano-pore structure and preparation method of corundum aggregate

    CN103253983A